1996
DOI: 10.1159/000259188
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Recovery of Chicken Distortion Product Otoacoustic Emissions following Acoustic Overstimulation

Abstract: Distortion product otoacoustic emissions (DPOAEs) were measured in chickens before and after exposure to a 525-Hz pure tone (120 dB SPL, 48 h). The exposure caused extensive hair cell loss and destroyed the tectorial membrane along the abneural edge of the basilar papilla in the low-to-mid-frequency region of the cochlea. Although the lesion was restricted, DPOAEs were greatly depressed at all frequencies immediately after the exposure. The high-frequency DPOAEs gradually recovered to preexposure values after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The maximum level reported here is approximately 10 dB higher than in our previous report since a higher current level was employed . As a point of comparison, the maximum EEOAE level is close to the maximum DPOAE that can be elicited from chickens using acoustic stimulation [Froymovich et al, 1995;Trautwein et al, 1996b]. The frequency response of our EEOAE had band pass characteristics with a peak near 3.5 kHz ( fig.…”
Section: Discussionsupporting
confidence: 54%
“…The maximum level reported here is approximately 10 dB higher than in our previous report since a higher current level was employed . As a point of comparison, the maximum EEOAE level is close to the maximum DPOAE that can be elicited from chickens using acoustic stimulation [Froymovich et al, 1995;Trautwein et al, 1996b]. The frequency response of our EEOAE had band pass characteristics with a peak near 3.5 kHz ( fig.…”
Section: Discussionsupporting
confidence: 54%
“…The effect of nonlinearity also appears in the compressive behavior of avian cochlear nerve rate-intensity functions (Richter et al 1995;KÖ ppl and Yates 1999;Yates et al 2000;Saunders et al 2002). In addition, acoustically or electrically evoked DPOAEs have provided another signature of nonlinear behavior (see, e.g., KÖ ppl 1995;Trautwein et al 1996;Chen et al 2001).…”
Section: Is the Stc A Proxy For Cochlear Mechanics?mentioning
confidence: 99%
“…Finally, the residual functional deficits observed after functional recovery from sound trauma correlate better with the area of the papilla over which recovery of the upper fibrous layer of the tectorial membrane was incomplete than with the area of lost and regenerated hair cells. This holds for DPOAEs [Froymovich et al, 1995;Trautwein et al, 1996b], behavioral temporal integration , pure-tone masking , TTRS Salvi et al, 1998] and the rateintensity functions of single auditory nerve fibers [Saunders et al, 1996a, b].…”
Section: Functional Regeneration and The Tectorial Membranementioning
confidence: 99%
“…This hypothesis was falsified, however, by the observation that, in adult chickens, the EP did not break down after sound trauma that caused severe global hearing loss at all frequencies . Thus although reduced EP, when it occurs, contributes to threshold elevation [Vossieck et al, 1991], other causes must be responsible for the global threshold elevation observed after sound trauma [Chen et al, 1996b, c;Trautwein et al, 1996bTrautwein et al, , 1997.…”
Section: Recovery Outside the Region Of Hair Cell Loss And Tectorial mentioning
confidence: 99%